2017
DOI: 10.1159/000464292
|View full text |Cite
|
Sign up to set email alerts
|

ENETS Consensus Guidelines for the Standards of Care in Neuroendocrine Tumours: Surgery for Small Intestinal and Pancreatic Neuroendocrine Tumours

Abstract: The small intestine and pancreas are among the most frequent abdominal sites of origin of neuroendocrine tumours. Distinctive features of these forms are represented by the relatively low incidence and the wide heterogeneity in biological behaviour. In this light, it is difficult to standardize indications for surgery and the most appropriate approach. It would be helpful for surgeons managing patients with these tumours to have guidelines for surgical treatment of small intestinal neuroendocrine tumours and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
260
0
22

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 255 publications
(295 citation statements)
references
References 94 publications
(141 reference statements)
4
260
0
22
Order By: Relevance
“…Preoperative tests should include computed tomography (CT) or MRI, somatostatin receptor scintigraphy (SRS) or 68 gallium positron-emission tomography (PET)/CT, 5-hydroxyindoleacetic acid (5-HIAA) levels in 24-h urine sample, and echocardiogram for assessing the burden due to carcinoid syndrome (10). The main scope of this workup is the prevention of perioperative carcinoid crisis presenting with hyperthermia, shock, arrhythmias, hyper-or hypotension, tachy-or bradycardia, flushing or bronchospasm.…”
Section: Preoperative Carementioning
confidence: 99%
See 4 more Smart Citations
“…Preoperative tests should include computed tomography (CT) or MRI, somatostatin receptor scintigraphy (SRS) or 68 gallium positron-emission tomography (PET)/CT, 5-hydroxyindoleacetic acid (5-HIAA) levels in 24-h urine sample, and echocardiogram for assessing the burden due to carcinoid syndrome (10). The main scope of this workup is the prevention of perioperative carcinoid crisis presenting with hyperthermia, shock, arrhythmias, hyper-or hypotension, tachy-or bradycardia, flushing or bronchospasm.…”
Section: Preoperative Carementioning
confidence: 99%
“…Dissection of at least eight (10,14,20) or 12 (23) lymph nodes has a positive impact on survival. A recent metaanalysis showed that among patients with metastatic disease, palliative resection of the primary tumor conferred a survival benefit (24).…”
Section: Locoregional Enterectomy With Lymph Node Dissectionmentioning
confidence: 99%
See 3 more Smart Citations